INSTALLATION OF ISLAMIC CHARACTER VALUES THROUGH STORYTELLING ACTIVITIES IN UMMI FAUZIAH RANTAUPRAPAT PAUD CHILDREN - Wahyuni, Ely; Prayoga, Yudi; Halim, Abd. (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Storytelling as a medium for cultivating Islamic characters in early childhood. The inculcation of Islamic character values ​​is the provision of an education that forms morals or manners that distinguish one person from another. The purpose of this PKM is to obtain data and information regarding abilities in storytelling activities, and the application of storytelling methods to instill Islamic character values ​​in early childhood. The type of approach used is a qualitative descriptive approach by taking observation data sources, interviews, and documentation. The expected result of this PKM activity is the formation of Islamic character in early childhood through storytelling activities. This PKM was held at Ummi Fauziah Kindergarten/PAUD in Padang Matinggi. From this activity, all participants gained knowledge and skills in instilling Islamic character values ​​through storytelling activities to improve quality and professionalism.